The Role of Financial Markets in Hydrogen Adoption - Florian Horky; Simona Bigerna; Paolo Polinori; Dimitrios Dimitriou; Cosimo Magazzino (European Financial Management, 2025)
This paper empirically investigates the role of financial markets (FM) and their development in promoting hydrogen adoption as a component of green and just transition. Hydrogen can play a significant role in the energy transition, especially for sectors that are otherwise hard to decarbonize. Utilizing a twofold methodology, we demonstrate that well-developed FM significantly drive hydrogen production. Moreover, the findings highlight the connection between individual hydrogen Exchange Traded Funds and high-tech stocks, while actual hydrogen pricing is connected to oil and gas. Policy implications highlight the need for clear regulatory frameworks, communication and blended financing support for hydrogen adoption.
Keywords: 650; financial development; financial ecosystem; financial markets; green transition; hydrogen; stock markets